Retail Payment Techniques and Their Impact on the Volume of Bank Deposits - Jawad, Mohammed Majeed; Khaleel, Ameer Ali; Neamah, Asmaa Hadi; Hasan, Mohammed Faez (Technium Business and Management, 2023)
The aim of the research is to demonstrate retail payment techniques using various electronic payment cards issued by banks. The research sample is in the Iraqi banking environment and to analyze the extent of its contribution to enhancing the volume of bank deposits, and then to know the relative importance of the volume of deposits between banks, the research sample. The research started from the problem of whether the volume of bank deposits is The most affected by the adoption of retail payment techniques by the banks of the research sample, and does their adoption really lead to enhancing the volume of deposits in banks? This research was applied in some commercial banks operating in Iraq, as the temporal limits extended for a period of (15) chapters over a period of nearly four years, and the research used a set of statistical analyzes and tests using the statistical financial programs SPSSv.23 and EXCEL, and the research reached a set of results, the most important of which showed The results showed that 75% of the banks, the research sample, demonstrated the existence of an impact relationship between retail payment techniques and the path of the volume of their deposits, which means the importance of the electronic payment service for the bank's customers. In banks if they feel the ease of withdrawing their money and using it in their daily expenses.